PENGARUH BERAT LABUR DAN JENIS KAYU TERHADAP SIFAT FISIKA DAN MEKANIKA PAPAN LAMINASI - Febriana Tri Wulandari; Radjali Amin; I Gde Adi Suryawan Wangiyana (BRIN Publishing, 2022)
The world's demand for wood is increasing while the amount of solid wood production is decreasing with the depletion of forestsdue to illegal logging and conversion of forest functions as plantation land. To overcome these problems, it is necessary to do theefficiency of wood raw materials so that the use of solid wood can be reduced. One of the efficient ways to use wood raw materials isto utilize optimized wood industrial waste by combining one or more types of wood which are glued together into a single unit,commonly called a laminated board. In this study, we will look at the effect of different types of wood and the weight of the gluespread on the resulting laminated board. Advantages Laminate board can produce a board size that is wide and long as neededbecause the joints are made as long as needed. In the manufacture laminated boards are made with the type of wood, namely jatiputih (Gmelina arborea. Roxb), bajur (Pterospermum javanicum), sengon (Paraserianthes falcataria) and mixtures(jati putih, bajur and sengon) and the glue spread factor is 150 g and 200 g. Then the physical and mechanical properties weretested. The test results showed that the wood type had a significant effect on all physical and mechanical properties except for thethickness shrinkage and MoE tests. The interaction of the lamination glue spread factor and the wood type factor did not significantlyaffect all physical and mechanical properties of mixed wood waste laminated boards. Based on the test results, laminated board isclassified as strong class III which can be used as a lightweight construction material indoors.